Superman. Vol. 6, Imperius Lex - Tomasi, Peter (DC Universe rebirth., 2018)
"It's a game of thrones on Apokolips as the lords of the dreaded world battle each other to claim its rule. Lex Luthor is summoned back to the warring planet, and he will need Superman to help him reclaim a crown he did not ask for. As the conflict continues, a new warrior enters the battlefield: Lois Lane, Female Fury. May Granny Goodness have mercy on all their souls."--